Prognostic value and molecular mechanism of photodynamic therapy and apoptosis related gene FGFR1 in bladder cancer - Wang, Lei; Wang, Yanchun; Wang, Yanqing; Wang, Zhengwei; Cheng, Guangzhou; Xu, Zhunan; Liu, Xiaoqiang (Frontiers in Oncology, 2025)
PurposePhotodynamic therapy (PDT) is an innovative non-invasive therapy for human cancer treatment. The significance of apoptosis-related genes (ARGs) in the prognosis of bladder cancer (BLCA) has gradually emerged. Therefore, this study aims to investigate the prognostic significance and pathogenesis of PDT related genes (PDTRGs)-ARGs in BLCA cases.MethodsBased on the BLCA data in TCGA, PDTRGs-ARGs with prognostic value in BLCA patients were screened. Subsequently, the prognostic value and diagnostic performance of all candidate genes were evaluated by univariate Cox regression analysis and ROC curves. Then, GSEA, GSVA and immune microenvironment analysis were conducted based on candidate genes. Finally, the molecular mechanisms of key candidate genes in BLCA patients were initially explored by qRT-PCR, CCK-8 analysis, Transwell Assay and Western Blotting.ResultsA total of 5 ARGs-PDTRGs (EMP1, FGFR1, PLPPR4, JUN, TNFRSF25) were screened as prognostic biomarkers for BLCA. Survival analysis revealed significant differences in overall survival of the five prognostic biomarkers in the high/low expression groups. ROC curve analysis revealed that the five prognostic biomarkers had strong prognostic predictive ability. QRT-PCR proved that the expression of EMP1, FGFR1, PLPPR4 and JUN was obviously reduced, while TNFRSF25 was markedly increased in BLCA tissue samples and cell lines. The following research confirmed that FGFR1 inhibited the biological process of T24 cells by activating cGMP-PKG pathway.ConclusionFive ARGs-PDTRGs (EMP1, FGFR1, PLPPR4, JUN, TNFRSF25) were screened as prognostic biomarkers for BLCA. Among them, FGFR1 inhibits the biological process of T24 cells via activating cGMP-PKG pathway.